The balance between work and life for subjective well-being: A moderated mediation model - Zameer Ul Hasan; Muhammad Imran Khan; Tahira Hassan Butt; Ghulam Abid; Saqib Rehman (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The aim of this study is to investigate the association among work-life balance, intrinsic motivation, subjective well-being and job satisfaction among the healthcare professionals of Pakistan. Utilizing a sample of 301 Health Care Professionals, the authors tested the proposed relationships. Findings were constant with the hypothesized theoretical scheme, and mediated association between work-life balance and subjective well-being through job satisfaction was stronger when intrinsic motivation was high rather than low. Based on the findings, we suggest that the association between work-life balance and subjective well-being in Health Care Professionals is more complicated than was previously believed—thus yielding a pattern of moderated mediation. In brief, it was found that work-life balance enhances subjective well-being through job satisfaction when intrinsic motivation is low. We also discuss the theoretical contributions and practical implications of the research and directions for future studies.
Keywords: 650; intrinsic motivation; job satisfaction; subjective well-being; work-life balance